1979
DOI: 10.1210/jcem-49-4-616
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Glucose, Mannose, Galactose, and Fructose in Man*

Abstract: The effects of various hexoses upon immunoreactive insulin (IRI) secretion, glucose disposal, and gastric inhibitory polypeptide (GIP) release have been compared in 10 normal nonobese men. Rapid iv infusion (0.5 g/kg in 3 min) of D-mannose resulted in significant ITI release, the peak levels approaching those after D-glucose infusion. D-Galactose, however, was ineffective. The 60-min urine excretions of mannose, galactose, and glucose were 35 +/- 7%, 16 +/- 4%, and 5.5 +/- 0.7% (mean +/- SEM) of the administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…As in previous studies, 1,[8][9][10][11] the ingestion of a large amount of galactose resulted in a transient increase in glucose that was less than 1 mmol/L (18 mg/dL) compared with the initial glucose concentration. However, when compared with the glucose value obtained when the same subjects ingested water only, the ingested galactose clearly resulted in a persistently higher glucose concentration.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…As in previous studies, 1,[8][9][10][11] the ingestion of a large amount of galactose resulted in a transient increase in glucose that was less than 1 mmol/L (18 mg/dL) compared with the initial glucose concentration. However, when compared with the glucose value obtained when the same subjects ingested water only, the ingested galactose clearly resulted in a persistently higher glucose concentration.…”
Section: Discussionmentioning
confidence: 73%
“…Galactose injected intravenously did not stimulate an increase in insulin. 10 With an increase in the insulin and glucose concentration, a decrease in glucagon would be expected. This did not occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter context, several acute studies have shown that ingestion of galactose leads to increased satiety [3,4,10]. Furthermore, a chronic study involving intermittent intake of sugary drinks in women has shown that intake of galactose in substitution for glucose resulted in increased fat mobilization and oxidation [6], which would be consistent with the much lesser impact of galactose than glucose ingestion on circulating insulin [12][13][14][15]. These studies have led to the proposal that diets with galactose as a source of carbohydrates could be useful in the management of obesity and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 79%
“…Furthermore, the increase in cardiac output and reduction in total peripheral resistance observed after ingestion of glucose were markedly lower after galactose ingestion (p < 0.01). a low-glycemic index and a low-insulinemic response [12][13][14][15]. Indeed, several studies in healthy humans have shown that the ingestion of galactose elicits only small increases in plasma glucose and insulin, which are not different from those in response to fructose ingestion [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%